The role expectations of young women as wives after breast cancer treatment: A qualitative study - Wenjuan Gao; Qian Zhang; Dan Wang; Xiaoxu Li; Linping Zhang; Mengjiao Xu; Jing Han (International Journal of Nursing Sciences, 2024)
Objectives: Through the reflection of young breast cancer women on their selves and identities, we explored expectations of the wife role that they need to fulfill to return to their families, aimed to provide a reference basis for medical professionals to develop interventions related to cancer family rehabilitation. Methods: Descriptive phenomenological methods and purposive sampling were used. Young breast cancer patients and their spouses were selected for semi-structured face-to-face interviews in the study from March to April 2023 at the department of breast surgery and oncology center of a Class A tertiary hospital in Xuzhou City, China. The interviews were transcribed verbatim and analyzed using Colaizzi’s phenomenological approach. Results: Twenty patients and six spouses were interviewed. The mean patient age was (35.95 ± 3.36) years, and the mean spouse was (37.67 ± 5.28) years. Young breast cancer patients were concerned about three main wife expectations during their treatment and rehabilitation: preserving self-love and self-esteem (paying attention to physical health, embracing the disease, and regaining confidence in female characters); adjustment of conjugal relationships (harmonious and effective couple communication, providing support for marriage and love, and creating a beautiful married life together); assisting in family recovery (relieving stress on spouses from caregiving and finances, and management of daily household chores). Conclusions: The wife role expectations of young breast cancer women and their spouses encompass three core aspects: self, couple, and family. Self-esteem and self-love are the most fundamental expectations of the wife role, while adjusting the couple’s relationship and assistance in family rehabilitation represent higher expectations. This study can help healthcare professionals and cancer families gain a more comprehensive understanding of the wife role expectations for young cancer women, thereby enabling the development of couple-centered interventions to promote patient recovery and enhance the resilience of marriages and families.